Analisis Miskonsepsi Peserta Didik Menggunakan Certainty of Response Index (CRI) pada Materi Stoikiometri - Wiwiana, Wiwiana; Hasri, Hasri; Husain, Halimah (Program Pasca Sarjana UNM, 2020)
Many students are misconception, so the researchers do research with the aims to analyze the level of understanding of the participants’ concept students and the factors causing students’ misconceptions on the subject matter stoichiometry. Data collection uses open-ended diagnostic tests with a scale CRI with 18 numbers and interviews. The results showed the percentage of understanding concepts of 21% with a low percentage category, understand the concept but not sure at 7%, with the low category, the percentage of misconceptions of 12% with low categories and percentage do not understand the concept of 61% with a high category. Factors that cause misconception include a) students; c) how to teach.